Exploring the Phylogeny and Species Diversity of Chelidoperca (Teleostei: Serranidae) From the Western Pacific Ocean by an Integrated Approach in Systematics, With Descriptions of Three New Species and a Redescription of C. lecromi Fourmanoir, 1982 - Lee, Szu-Hsuan; Lee, Mao-Ying; Matsunuma, Mizuki; Chen, Wei-Jen (Frontiers in Marine Science, 2019)
With eleven species, the genus Chelidoperca is a small group of teleost fishes belonging to the Serranidae. They are bottom-dwelling fishes living on continental shelves/slopes in offshore areas or on remote seamounts/banks at depths ranging from around 40 to 400 meters mostly in the tropical Indo-West Pacific. Over the past few years, efforts have been made to resolve the taxonomy of Chelidoperca, and subsequently four new species were described. However, these recent advances were made with a traditional approach (i.e., morphology) and limited examinable materials, usually preserved specimens, from ichthyological collections. Further investigations are still needed to address the gaps in our knowledge about their diversity, phylogeny, and biogeography. In this study, we collected 64 new samples, mainly during eight biodiversity expeditions carried out between 2007 and 2016 in the West Pacific under the Tropical Deep-Sea Benthos program. Specimens were photographed after collection to record fresh color patterns, which are essential for species diagnosis. Our analytical approach includes state-of-the-art DNA-based methods for species delimitation. The combined evidence from both molecular and morphological examinations, as well as other information such as geography, is used to test species validity. This reveals 15 species, including six new ones. We formally describe herein C. leucostigmata sp. nov., C. microdon sp. nov., and C. barazeri sp. nov. on the basis of specimens collected on Macclesfield Bank in the South China Sea, on the Chesterfield and Island of Pines plateau of New Caledonia, and off the New Ireland Province of Papua New Guinea, respectively. These new species are morphologically distinct from all other known species of Chelidoperca by body color pattern and combinations of a few identified characters. We also redescribe one of the lesser known species, C. lecromi, from fresh specimens collected close to its type locality and a new site in the Coral Sea. The distributional records for this and other known species are updated accordingly. Genetic references of the species as well as an updated identification key to western Pacific species are also provided.